(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
The article describes a number of sculptured stones and crosses with a range of early Christian symbols including a double-disc or spectacle ornament with the Z-shaped line crossing it, a fish symbol with a triangle surrounding a central dot and an unusual triangle with a crescent across it. A standing stone at Nether Corskie has a mirror and comb alongside a mirror-case. The crosses are generally weathered with simple incised crosses and have almost all been re-used as building material.